Exploring The Challenges of Noisy Areas Faced by Teachers in Teaching and Learning in Urban Schools - Pervaiz, Atiya; Lashari, Ajab Ali; Khan, Asmara; Bushra, Amna (Pakistan Journal of Humanities and Social Sciences, 2024)
This research study aimed to explore the challenges encountered by teachers teaching in urban areas and noisy surroundings, leading to several issues in achieving required learning outcomes. For this purpose, the qualitative research approach of phenomenological research was used, and data was collected using in-depth semi-structured interviews. The population of this research study was primary school teachers of Mominabad, Karachi. Using purposive sampling techniques, N=10 teachers from n=3 schools were selected. Data was collected by using semi-structured interviews. The study results show that unusual noise distractions impact students' learning and distraction concentration, which affects cognitive development and hinders effective communication between teachers and students, leading to anxiety and waste of time and energy. Furthermore, it has been found that children exposed to continuous disruptive noise can experience poor reading ability, memory and academic performance, which may lead to failure in the educational process. It is recommended that there is a need for strategies to mitigate noise effects, such as considering infrastructure, implementing soundproofing measures, utilising technology to enhance communication, and providing training and support for teachers to manage the challenges posed by noise pollution.